ANALISIS GAYA BAHASA PADA NOVEL MIDAH SIMANIS BERGIGI EMAS KARYA PRAMOEDYA ANANTA TOER - Laila, Hasya Tsalist; Hidajat, Putri Balqis Rizkita; Damayanti, Welsi (Universitas PGRI Adi Buana Surabaya, 2025)
Analyzing the comparative language style used in the novel Midah Simanis Bergigi Emas by Pramoedya Ananta Toer is the purpose of this research. The method used for this research is descriptive qualitative method. The data is collected by applying reading technique and note-taking technique. The results of the analysis are listed in the form of speech contained in the novel Midah Simanis Bergigi Emas by Pramoedya Ananta Toer. The results of the analysis of the comparative language style in the novel Midah Simanis Bergigi Emas by Pramoedya Ananta Toer were found 90 quotations, consisting of: 43 quotes using metaphorical language style, 6 quotes using allegory language style, 6 quotes using simile language style, and 35 quotes using personification language style.